(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to improve the motivation to learn mathematics in VII grade students of SMP Negeri 3 Terangun through the Realistic Mathematics Education (RME) approach in Social Arithmetic material. The method in this research is a class action method consisting of 2 cycles. Each cycle includes the planning stage, the stage of implementing actions and observations, and the reflection phase. The subjects of this study were Grade VII students of SMP Negeri 3 Terangun in the 2019/2020 school year with a total of 36 students. Retrieval of this data using a questionnaire at the end of the cycle. As an indicator of the success of this study is the level of high motivation learning criteria that is 75.00% ≤ X ≤ 100%. The results of the research questionnaire presented in the first cycle were 61.75% and the second cycle obtained 77.35%. In accordance with the results of the cycle, the desired or expected target of researchers has been achieved. The core of this study is through the Realistic Mathematics Education (RME) approach in Social Arithmetic material can improve motivation to learn mathematics.